1987
DOI: 10.1161/01.str.18.5.830
|View full text |Cite
|
Sign up to set email alerts
|

Disability and use of rehabilitation services following stroke in Rochester, Minnesota, 1975-1979.

Abstract: Medical records of all residents of Rochester, Minnesota, who had a first stroke in 1975-1979 were reviewed to determine level of disability, disposition, and use of rehabilitation services. Of the 292 persons with a first stroke, 251 (86%) (mean age 70 years) survived > 1 week. The mean Rankin disability score (Grade 1, no disability, through Grade 5, severe disability) changed from 1.7 before stroke to 2.8 in survivors at hospital discharge; 29% of those discharged required further institutional care. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
2
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 23 publications
6
52
2
5
Order By: Relevance
“…9,13,21,22 All studies adjusted for age, 2 adjusted for stroke severity, 21,22 and 2 adjusted for vascular risk factors. 13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments. 11 In contrast, others reported no association between sex and long-term functional outcomes in unadjusted analyses 11,12,20 or after adjusting for age, 16,18,[25][26][27][28][29][30][31] socioeconomic factors, 29 stroke severity, 17,18,25-27,29 -31 prestroke disability, 16,25,27 treatment, 27 mood, 18 and comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…9,13,21,22 All studies adjusted for age, 2 adjusted for stroke severity, 21,22 and 2 adjusted for vascular risk factors. 13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments. 11 In contrast, others reported no association between sex and long-term functional outcomes in unadjusted analyses 11,12,20 or after adjusting for age, 16,18,[25][26][27][28][29][30][31] socioeconomic factors, 29 stroke severity, 17,18,25-27,29 -31 prestroke disability, 16,25,27 treatment, 27 mood, 18 and comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…6 Similarly, a larger number of comorbidities correlated with poorer mRS scores 1 year poststroke in patients at the Mayo Clinic. 10 These data suggest that functional outcome measures in stroke studies may need to be adjusted for prestroke comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…10 More than 50% of stroke survivors have significant residual physical disability and functional impairment. 12 Stroke recurrence not only may add to physical impairment and disability but may also increase mortality and length of hospital stay. 7 In addition, stroke recurrence may lead to vascular dementia or may be an important trigger for dementia in the elderly.…”
Section: Likelihood and Consequences Of Stroke Recurrencementioning
confidence: 99%